Intelligent agent technology in e-commerce - Goh, Ong Sing; Fung, C.C. (Springer Berlin, 2003)
Use of Internet has surged at an exponential rate in recent years. In particular, it has led to many new and innovative applications in the area of E-Commerce. In this paper, we introduce an intelligent agent termed AINI, the Artificial Intelligent Solution Humanoid. We also show how current e-commerce technological trends can be enhanced by using AINI. AINI is a chatterbot integrated with 3D animated agent character, Speech Technology and Artificial Intelligence Markup Language (AIML) is utilised. This agent technology is mainly used to improve customer services and to reduce customer reliance on human operators. By using artificial intelligence techniques, AINI is able to provide appropriate answers to service inquiries. In this paper, issues on Intelligent Agents Technology, Speech Technology, AIML and the use of 3D animated character in E-Commerce are discussed.